Geoeconomic analysis of the Chancay Hub Port: challenges and opportunities - Maúrtua de Romaña, Oscar (2024)
The complexity of international relations is deepened, among other factors, due to the growing economic interdependence, which has spread to all the areas that make up world society. This has become a greater link and rapprochement between the main actors operating in this scenario, especially, from the use of the sea route. In the Peruvian case, significant transformations have been generated in the port system, such as the construction of a new port and logistics complex in the city of Chancay. This mega project, although it will position Peru as a relevant geopolitical actor in the region, poses a challenge around the geoeconomic potential that can be developed, for which our decision makers need to be strategically and timely informed. In this sense, the present work aims to offer a geoeconomic analysis around the potential advantages and challenges posed by the construction of this megaproject, emphasizing that local territorial development strategies and economic opportunities generated from global initiatives such as the Strip and the Route, will insert Peru into the main global value chains. To achieve this purpose, a bibliographic review of the main working documents and specialized literature on the subject will be carried out, with the purpose of finding empirical evidence that contrasts the hypothesis.